2012
DOI: 10.1175/jcli-d-11-00209.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sea Ice Thickness Distribution in the Arctic Sea Ice Potential Predictability: A Diagnostic Approach with a Coupled GCM

Abstract: The intrinsic seasonal predictability of Arctic sea ice is investigated in a 400-yr-long preindustrial simulation performed with the Centre National de Recherches Météorologiques Coupled Global Climate Model, version 3.3 (CNRM-CM3.3). The skill of several predictors of the pan-Arctic sea ice area was quantified: the sea ice area itself, the pan-Arctic sea ice volume, and some areal predictors built from the subgrid ice thickness distribution (ITD). Sea ice area provides a potential predictability of about 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 35 publications
(41 reference statements)
10
100
1
Order By: Relevance
“…3a-c), which is consistent with Chevallier and Salas y Mélia (2012). Conversely, the OHC AO has more persistent negative correlations with the SIE AO in winter than in summer (Fig.…”
Section: Possible Mechanisms For Prediction Skillsupporting
confidence: 86%
See 1 more Smart Citation
“…3a-c), which is consistent with Chevallier and Salas y Mélia (2012). Conversely, the OHC AO has more persistent negative correlations with the SIE AO in winter than in summer (Fig.…”
Section: Possible Mechanisms For Prediction Skillsupporting
confidence: 86%
“…The observed detrended Arctic sea ice extent, based on ensemble hindcasts can be predicted up to 2-7 and 5-11 months ahead for summer and winter, respectively (e.g., Chevallier et al, 2013;Sigmond et al, 2013;Wang et al, 2013;Msadek et al, 2014;Peterson et al, 2015;Guemas et al, 2016;Sigmond et al, 2016). In these ensemble hindcasts, it is found that ice thickness and surface or subsurface water temperatures are closely related to the prediction skill, as suggested by idealised or perfect-model experiments with climate models (e.g., Blanchard-Wrigglesworth et al, 2011b;Chevallier and Salas y Mélia, 2012;Day et al, 2014a).…”
Section: Introductionmentioning
confidence: 87%
“…A recent study by Inoue et al (2012) suggested that the meridional temperature gradient due to ice variations in the Barents Sea is the main reason for the observed SLP anomalies and the connected "warm Arctic-cold continent" temperature patterns in recent years. A number of studies showed predictability of sea ice anomalies up to 6 months and more Tietsche et al 2014;Chevallier and Salas-Mélia 2012;Blanchard-Wrigglesworth et al 2011a, b;) mainly due to persistence, reemergence and advection processes. Thus, September and even more November sea ice anomalies (Chevallier et al 2013) could lead winter ice anomalies, which in turn affect the meridional temperature gradient and thus atmospheric circulation.…”
Section: Meridional Temperature Gradientmentioning
confidence: 99%
“…Most of analyses dealing with the Arctic sea ice cover seasonal predictability are based on statistical relationships (Walsh et al 1980;Johnson et al 1985;Drobot and Maslanik 2002;Drobot 2007), giving relatively good prediction scores. It seems, however, that non-observable variables-such as, for example, sea ice thickness (SIT) distribution-appear to be the best predictors of sea ice cover (extent or volume) (Chevallier and Salas y Mélia 2012). Further, considering the rapid changes in the Arctic environment, statistical relationships may not remain valid in the future (Holland and Stroeve 2011), justifying the increasing use of physical models.…”
Section: Introductionmentioning
confidence: 99%